Alkylation of Nitroarenes via Vicarious Nucleophilic Substitution – Experimental and DFT Mechanistic Studies. Issue 46 (29th June 2022) - Antoniak, Damian; Pałuba, Bartosz; Basak, Tymoteusz; Błaziak, Kacper; Barbasiewicz, Michał
Abstract: Alkylation of nitroarenes via Vicarious Nucleophilic Substitution (VNS) was tested experimentally and modelled with DFT calculations. Mechanistic studies reveal intrinsic differences between reactions of archetypal carbanion precursor PhSO2 CH2 Cl, and alkyl phenyl sulfones, in which benzenesulfinate acts as a leaving group. Accordingly, for the latter precursors steric hindrance develops at the β‐elimination step, that raises energy barrier and results in the formation of byproducts. Abstract : Alkylation of nitroarenes via Vicarious Nucleophilic Substitution (VNS) was tested experimentally and modelled with DFT calculations. Mechanistic studies reveal intrinsic differences between reactions of archetypal carbanion precursor PhSO2 CH2 Cl, and alkyl phenyl sulfones, in which benzenesulfinate acts as a leaving group. Accordingly, for the latter precursors steric hindrance develops at the β‐elimination step, that raises energy barrier and results in the formation of byproducts.